Dendritic Cells: Versatile Players in Renal Transplantation - Lin, Jinwen; Wang, Hongyi; Liu, Chenxi; Cheng, Ao; Deng, Qingwei; Zhu, Huijuan; Chen, Jianghua (Frontiers in Immunology, 2021)
Dendritic cells (DCs) induce and regulate adaptive immunity through migrating and maturing in the kidney. In this procedure, they can adopt different phenotypes--rejection-associated DCs promote acute or chronic injury renal grafts while tolerogenic DCs suppress the overwhelmed inflammation preventing damage to renal functionality. All the subsets interact with effector T cells and regulatory T cells (Tregs) stimulated by the ischemia-reperfusion procedure, although the classification corresponding to different effects remains controversial. Thus, in this review, we discuss the origin, the maturation, and the pathological effects of DCs in the kidney. Then we summarize the roles of divergent DCs in renal transplantation: taking both positive and negative stages in ischemia-reperfusion injury (IRI), switching phenotypes to induce acute or chronic rejection, and orchestrating surface markers for allograft tolerance via alterations in metabolism. In conclusion, we prospect that multidimensional transcriptomic analysis will revolute researches on renal transplantation by addressing the elusive mononuclear phagocyte classification and providing a holistic view of DC ontogeny and subpopulations.